Frame Selection and Adjustment of Progressive Long Corridor Lens Glasses for Presbyopia - David, David; Dasuki, Ahmad; Ruslan, Eriko; Haryanti, Suci (UNIVERSITAS INDRAPRASTA PGRI, 2024)
Presbyopia and explains why people need reading glasses as they age. Progressive lenses correct presbyopia. Only in this case study Client uses progressive lens with size: R/ : + 1.00 Cyl-0.50 x95 L/ : +1.00 Cyl-0.25 x80 ADD : +2.25 Progessive long corridor lens PD : 63/60 Size frame (A) : 53 mm Pupil Height (PV): 18 mm Vertical (B): 35 mm. Initial frame: A 51mm B 43mm ED 52mm D 17mm without nosepad.at the back (bend down) the MPD (monocular pupil distance) point is still not right. Because the frame is made of plastic and there is no nosepad, it cannot be adjusted to the nosepad. So that the replacement of the frame that has a nosepad with the following data: Frame type: full frame, Frame material: combination of plastic and metal, Data frame: A 50mm, B 44mm, ED50mm, D 21mm, Lens Type: progressive long corridor. Face adjustments are made to carry out MRP (Major Reference Point) pins on clients. For frames with a nosepad, it is more opened so that the vertex distance is closer, so that the close vision is wider (key hole principle). Then the bend down is bent so that the glasses do not go down when used.